Biomechanical effect of anterior talofibular ligament injury in Weber B lateral malleolus fractures after lateral plate fixation: A finite element analysis. Issue 8 (December 2020) - Zhou, Lin; Lin, Jiaming; Wang, Bata; Gan, Weidong; Huang, Anfei; Lin, Yongxin
Highlights: The anterior talofibular ligament injury is a major contributing factor to the stress of lateral plate fixation following Weber B lateral malleolus fracture. Anterior talofibular ligament plays a pivotal role in the biomechanical environment of lateral malleolus. Anterior talofibular ligament should be considered as an essential risk factor for evaluation of the stability in Weber B lateral malleolus fracture. Clinicians should pay more attention to the currently neglected injury of the anterior talofibular ligament in the clinical diagnosis and treatment of Weber B lateral malleolus fracture. Abstract: Objective: To determine the biomechanical effect of anterior talofibular ligament injury in Weber B lateral malleolus fractures after lateral plate fixation. Method: A three-dimensional model was established based on CT images from a healthy volunteer. The simulation of lateral malleolus fracture, and the modeling and assembly of plate were completed by referring to characteristics of Weber B lateral malleolus fractures, as well as the technical characteristics of open reduction and internal fixation of lateral plate. Operating conditions were set up for groups A−D. The proximal end of the model was restrained in all four groups, 200 N of upward force and 100 N of backward force were applied at anterior of talus head in order to simulate the dorsiflexion of ankle joint. Biomechanical differences of the lateral plate were observed under various conditions of different ligament ruptures. Results: The maximum stress value of group A was the smallest, approximately 78.47 N, while that of group C was the largest, approximately 238.83 N. The maximum stress value of group B was about 91.69 N; and that of group D was about 184.08N. Importantly, location of the maximum stress in group D (CUT ATaF) was displaced from the posterior edge to the anterior edge of the plate, which was different from those of the other three groups. Conclusions: The anterior talofibular ligament injury may be a major contributing factor to the stress of lateral plate fixation following Weber B lateral malleolus fracture. It should be considered as an essential risk factor for evaluation of the stability in these fractures.